Metaphor across Time and Conceptual Space : the Interplay of Embodiment and Cultural Models - Mischler, III, James J. (Cognitive inguistic Studies In Cultural Contexts ;, 2013)
Contemporary linguistic forms are partially the product of their historical antecedents, and the same is true for cognitive conceptualization. The book presents the results of several diachronic corpus studies of conceptual metaphor in a longitudinal and empirical "mixed methods" design, employing both quantitative and qualitative analysis measures; the study design was informed by usage-based theory. The goal was to investigate the interaction over time between conceptualization and cultural models in historical English-speaking society. The main study of two linguistic metaphors of anger spa.